Spatial analysis of amyotrophic lateral sclerosis in Northern New England, USA, 1997–2009. Issue 2 (23rd July 2013) - Caller, Tracie A.; Chipman, Jonathan W.; Field, Nicholas C.; Stommel, Elijah W.
ABSTRACT: Introduction: An environmental trigger of sporadic amyotrophic lateral sclerosis (ALS) is supported by geographic disparities in ALS incidence and development of the disease in conjugal couples. This study aims to investigate the incidence of ALS in the Northern New England states of New Hampshire (NH), Vermont (VT), and Maine (ME). Methods: We reviewed medical records and community databases to identify dwelling addresses of 688 patients diagnosed with ALS in 1997–2009 in NH, VT, and ME. We used spatial analysis to identify clusters of census block groups with statistically significant high incidence. Results: We identified 11 clusters of statistically significant high incidence, each containing 6 or more cases of ALS. These 11 clusters are grouped in 4 distinct regions. Conclusions: There appear to be areas of significant spatial clustering within Northern New England. Further analysis will be needed to confirm whether there is any correlation between these areas and potential environmental risk factors. Muscle Nerve, 48: 235–241, 2013